Growth Model for Biodegradation of VOCs in Batch and VOCs Removal from Contaminated Air in Biofilter Using Pseudomonas putida and Isolated Strain NTPM1 - D. Najafpour, Ghasem; Yok Mian, Yap (Asian Journal of Chemistry, 2016)
Biodegradation of VOGs is polluted air was investigated in biofilter. Biofilter was a kind of continuous process loaded with active cells. Pseudomonas putida F1 and isolated strain NTPM1 were immobilized in packed bed biofilter. Contaminated air, contained acetone was biologically oxidized by passing through the biofilter. The filter medium with an active biofilm was acting as effective absorbing surface. Extensive studies were conducted to determine removal efficiency of the biofilter. Acetone-air flow rate with acetone concentrations of 8 to 16 g/L, was set at 100, 200 and 300 cm3/min equivalent to empty bed residence time of 2, 3 and 6 min, respectively. At air flow rate of 100 cm3/min, maximum acetone removal efficiency of 90% was obtained. In batch experiment, low concentration of acetone in the range of 150–550 mg/L and phenol, also 150–950 mg/L of hexane, benzene and toluene with an increment of 100 mg/L were used. P. putida F1 and isolated strain NTPM1 were compared. P. putida F1 showed higher removal efficiency in shorter period of time in comparison to isolated strain NTPM1. The batch results demonstrate the treatability and efficient removal of acetone, phenol, hexane, benzene and toluene in the biofilter at high concentration of 16 g/L. A growth model, based on microbial biodegradation of VOCs in batch process was developed.